Greater Exercise Sweating in Obese Women with Polycystic Ovary Syndrome Compared with Obese Controls - STACHENFELD, NINA S. (2010)
PURPOSE: We examined estradiol and testosterone effects on thermoregulation in women with and without Polycystic Ovary syndrome (PCOS). We hypothesized that core temperature (T(c)) threshold for sweating during exercise is delayed in women with PCOS and that testosterone delays the T(c) set point for sweating during exercise. METHODS: For 16 d, we suppressed estrogens, progesterone, and testosterone with a gonadotropin-releasing hormone antagonist (GnRHant) in seven women with and seven women without PCOS (control); we added 17β-estradiol (0.2 mg·d(-1), two patches) on days 4–16 (E(2)) and testosterone (2.5 mg·d(-1), orally) on days 13–16 (E(2) + T). Under each hormone condition, subjects cycled in a temperature of 35°C at 60% of age-predicted HR(max) for 40 min. RESULTS: T(c) sweating threshold was lower in women in the PCOS group compared with those in the control during GnRHant (37.21°C ± 0.51°C vs 37.70°C ± 0.12°C, P < 0.05); neither E(2) nor E(2) + T influenced the thermoregulatory responses in PCOS. E(2) decreased T(c) sweating threshold in control (37.06°C ± 0.69°C, P < 0.05), but E(2) + T attenuated this response (37.53°C ± 0.19°C). Peak sweating rate was greater in women in the PCOS group compared with those in the control group during GnRHant (1.06 ± 0.47 vs 0.47 ± 0.11 mg·cm(-2)·min(-1)) and E(2) + T (0.85 ± 0.41 vs 0.44 ± 0.10 mg·cm(-2)·min(-1), P < 0.05). Compared with the control group, total sweat losses were greater in the PCOS group during GnRHant (0.614 ± 0.189 vs 0.419 ± 0.098 L) and during E(2) + T (0.696 ± 0.281 vs 0.434 ± 0.164 L, P < 0.05) but not during E(2) (0.639 ± 0.231 and 0.505 ± 0.214 L for PCOS and control groups, respectively, P = 0.09). CONCLUSIONS: Thermoregulation was adequate in women with PCOS; however, the women with PCOS achieved thermoregulation at the expense of producing higher sweat volumes.